Implementing Collaborative Writing to Improve High School Students' Grammar - Candraning Prihatini (Universitas Muhammadiyah Lampung, 2024)
This study aims to analyse the errors that occur in the English writing of third-semester students of the Law Study Programme at UIN Syarif Hidayatullah in the English MKDU course. Using a descriptive qualitative approach, this research involved 24 students who were asked to spontaneously write a short essay on a general academic topic. The data were analysed using the Dulay, Burt, and Krashen error taxonomy, which includes omission, addition, misformation, and misordering, complemented by an analysis of vocabulary, spelling, and coherence aspects. The results indicate that grammar errors are the most common category, followed by vocabulary errors, sentence structure, spelling, and paragraph coherence. The findings also reveal that interference from the Indonesian language, limited mastery of basic grammar, limited exposure to English, and reliance on translation tools are the primary factors causing these errors. Overall, this research emphasises the need for a more integrated writing learning approach that focuses on developing linguistic competence, rhetorical strategies, and meaningful feedback to enhance the writing skills of non-English language students.